CONSTRUCTION OF THE SUCCESS FACTORS OF IKAT WEAVINGS (A CASE STUDY OF AN IKAT WEAVING CRAFTSMAN UNDER THE BIA BEREK IKAT WEAVING GROUP – BELU REGENCY) - Mau, Ignatia Thomasita Bau; Djazuli, Atim; Djawahir, Helmy (Jurnal Ilmu Sosial dan Humaniora, 2021)
This study discusses the success factors in running a woven handicraft business experienced and immediately felt by several ikat craftsmen in one group of Bia Berek weaving in the city of Atambua, Belu Regency, East Nusa Tenggara. This is to direct the informant to answer all the success factors that have occurred and let the qualitative research model be used as a method in this research. The research used semi-structured interviews, and the informant reveals as widely as possible the informant regarding other factors that are also the key to success in running a business. These success factors include the proper management of current assets (supplies of woven fabrics) and fixed assets (weaving equipment and equipment and business premises), the ability to manage business turnover, cash flow management, the ability to process all business costs in the cost structure, management of revenue on weaving business, having personal savings and investing in non-bank financial services, increasing the marketing of woven fabrics, using technology for business innovation in the digital world, prioritizing the quality of woven fabrics produced, utilizing culture and tradition as business opportunities and potential, building profitable cooperation with local government of Belu Regency. The twelve factors that have been classified into financial and non-financial factors are constructed in a new model design that can be used as learning materials for micro, small and medium enterprises in improving their business by taking into account all the success factors that occur in their business.